Осесимметричное упругопластическое состояние составных оболочек при термосиловом нагружении и радиационном облучении - Бабешко, М.Е.; Савченко, В.Г. (Прикладная механика, 2017)
Запропоновано методику чисельного дослідження термопружнопластичного вісесиметричного напружено-деформованого стану тонких шаруватих оболонок з ізотропних і трансверсально-ізотропних матеріалів за термосилового навантаження. Використано визначальні рівняння теорії термопластичності для ізотропних матеріалів і теорії пружності для трансверсально-ізотропних матеріалів. Наведено результати розрахунку пружнопластичного стану двошарової пластини з урахуванням впливу радіації та надано їх аналіз. A technique of numerical study is proposed as applied to the thermoelastoplastic axisymmetric stress-strain state of thin layered shells made of the isotropic and transversally isotropic materials under thermo-force loading and irradiation. The constitutive equations of the thermoplasticity theory for isotropic materials and the theory of elasticity for transversally isotropic materials are used. Some results of evaluation of the elastoplastic state of two-layered plate are shown with allowance for irradiation that are further analyzed.